FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Valentina Lesmana, Bella; Effendi, Muhammad Arief (E-Jurnal Akuntansi TSM, 2023)
The purpose of this research is to analyze the effect of the independent variables, current ratio, debt to equity ratio, return on asset, firm size, institutional ownership, and managerial ownership on the dependent variable of firm value. The population of the sample in this research used from manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2018 to 2020. The sample used and selected based on the purposive sampling method from the data collected, which obtained 73 manufacturing companies that met the criteria. The analytical method used in this research is multiple regression analysis method. The result of the study prove that the current ratio, firm size, institutional ownership, and management ownership have no effect on firm value, while other independent such as debt to equity ratio, return on asset, and firm size have an influence on firm value.